Heat transfer characteristics of metallic body during quenching in saturated nanofluids - Hazirah, Ismail; Muhamad Zuhairi, Sulaiman; Okawa, Tomio (Universiti Malaysia Pahang, 2022)
Heat transfer characteristics (HTCs) of a metallic rod during quenching were investigated in saturated water-based nanofluids and the results were compared to distilled water. In this study, a 50 mm length of cylindrical copper rod with a diameter of 15 mm was rapidly quenched at an initial temperature of 600 ℃ in saturated water-based nanofluids under atmospheric pressure. Three different types of nanoparticles (Al2O3, SiO2 and TiO2) were used to obtain water-based nanofluids with 0.001% particle volume fraction. In this experiment, heat transfer rates were evaluated using the cooling curves (temperature vs time) of the copper rod quenched in different quenching media. Results showed that the quenching heat transfer in nanofluids was stochastic during the first quenching, with SiO2 showing a deterioration in HTC, enhancement was observed in Al2O3 and TiO2 compared to distilled water in the present work. However, after successive quenching, from second to seventh, all nanofluids demonstrated enhancement in the cooling time, with quenching in TiO2 nanofluid showing the most significant enhancement compared to distilled water. Some deposition of nanoparticles on the surface of the rod was noticed, due to oxidation in distilled water quench, and mixed oxidation and nanoparticles deposition in the nanofluid quench. The present work suggested oxidation lead to deterioration of HTC, but a mixed effect of oxidation and nanoparticles deposition during the quenching process, altered the surface roughness of the rod surface and improved wettability. Hence, it was possible that the effect of surface structure vapour during film boiling influenced the dynamics of the bubbles in nucleate boiling and therefore enhanced the rapid cooling of the rod.